Development of a problem-based learning module on data presentation to enhance students' mathematical representation ability - Huznul Hidayatul Putri; Putri Yuanita; Titi Solfitri (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
This study aimed to develop and validate a mathematics teaching module on data presentation content based on the Problem-Based Learning (PBL) model to facilitate the mathematical representation ability of Phase D (Grade VII) students. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. Research instruments consisted of expert validation sheets and student response questionnaires. The validation results indicate that the developed module achieved an average expert score of 91.11%, categorized as very valid. Practicality testing showed average student response scores of 91.17% in the small-group trial and 86.93% in the large-group trial, indicating that the module is highly practical. These findings suggest that the developed PBL-based teaching module is feasible for classroom implementation and effective in supporting students' mathematical representation ability in data presentation learning. This study contributes to the development of contextual instructional materials based on PBL and provides a foundation for future research examining the effectiveness of the module through experimental designs.